2008
DOI: 10.1073/pnas.0801717105
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of antibody-mediated presentation of antigen on FcRn

Abstract: The neonatal Fc receptor for IgG (FcRn) is a distant member of the MHC class I protein family. It binds IgG and albumin in a pHdependent manner and protects these from catabolism by diverting them from a degradative fate in lysosomes. In addition, FcRn-mediated IgG transport across epithelial barriers is responsible for the transmission of IgG from mother to infant and can also enhance IgG-mediated antigen uptake across mucosal epithelia. We now show a previously undescribed role for FcRn in mediating the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
308
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(326 citation statements)
references
References 32 publications
13
308
2
2
Order By: Relevance
“…Kinetic rate values were calculated using predefined models (Langmuir 1:1 ligand model, heterogeneous ligand model, and steady-state affinity model) provided by using BIAevaluation 4.1 software. The closeness of the fit, described by the statistical value 2 , which represents the mean square, was lower than 2.0 in all affinity estimations.…”
Section: Construction Of Mutant Fcrn Variants-mentioning
confidence: 67%
See 1 more Smart Citation
“…Kinetic rate values were calculated using predefined models (Langmuir 1:1 ligand model, heterogeneous ligand model, and steady-state affinity model) provided by using BIAevaluation 4.1 software. The closeness of the fit, described by the statistical value 2 , which represents the mean square, was lower than 2.0 in all affinity estimations.…”
Section: Construction Of Mutant Fcrn Variants-mentioning
confidence: 67%
“…Moreover, the receptor plays a role in antibody-mediated antigen presentation by dendritic cells (2). FcRn has also been found to salvage albumin from intracellular degradation (3), in a fashion similar to that described for IgG, which involves receptor ligand interactions in acidified endosomal compartments (1).…”
mentioning
confidence: 99%
“…3,4 FcRn-IgG interaction also functions in antigen presentation and cross-presentation in macrophage and dendritic cells. 5,6 Each of these functions has important implications in therapeutic antibody development. Detailed review of the biology of FcRn function has also been covered elsewhere.…”
Section: Fundamental Biology Of Fcrnmentioning
confidence: 99%
“…35 In dendritic cells, FcRn can mediate antigen presentation and cross-presentation, functions that are critical for adaptive immunity and potential therapeutic immunization process. 5,6 Vascular endothelium. By conditional deletion of FcRn in mice using Cre recombinase under the control of the Tie2 promoter, it was demonstrated that FcRn in the vascular endothelium and hematopoietic cells are the major sites for maintaining IgG homeostasis.…”
Section: Fcrn Functions In Organsmentioning
confidence: 99%
“…FcRn has been detected in numerous types of polarized epithelia, including those from the intestines, lung, breast, and kidney, as well as other parenchymal cells, including hepatocytes, endothelial cells, and hematopoietic cells, where it is expressed in dendritic cells, monocytes, macrophages, polymorphonuclear leukocytes, and, perhaps, B cells (7,8). FcRn protects monomeric IgG and albumin from degradation in both parenchymal and hematopoietic cells, is responsible for the bidirectional transcytosis of IgG and IgG antigen/antibody complexes across polarized epithelia, and, finally, directs immune complexes to lysosomes in dendritic cells for facilitation of antigen presentation (9,10).…”
mentioning
confidence: 99%